Conflict Resolution Skills of Fifth-Grade Primary School Students: A Dimensional Analysis Based on Crawford and Bodine's Framework - Syahid Syahid; Ernawulan Syaodih; Wahyu Sopandi; Atep Sujana (Papanda Publisher, 2026)
Conflict resolution skills are critical social-emotional competencies for primary school students, yet the dimensional profile of these skills in the Indonesian context remains insufficiently documented. This study employed a quantitative descriptive survey design to examine the conflict resolution skills of 53 fifth-grade students at SDN 1 Karangreja and SDN 2 Karangreja, Karangreja District. Data were collected using a 54-item, four-point Likert scale questionnaire developed on the basis of Crawford and Bodine's (1996) six-dimensional framework, encompassing orientation, perception, emotional management, communication, creative thinking, and critical thinking skills. The instrument demonstrated satisfactory validity and high reliability (Cronbach's α = 0.87). Data were analysed using descriptive statistics. All six dimensions fell within the Moderate mastery category. Communication skills recorded the highest mean score (57.02%), followed by orientation (56.39%), while emotional management yielded the lowest score (43.19%). These findings indicate that students possess foundational but incomplete conflict resolution competencies, with relational-communicative skills more developed than affective and higher-order cognitive capacities — a pattern that challenges a strictly linear reading of Crawford and Bodine's developmental sequence. The study contributes a theoretically grounded, empirically differentiated competency profile to the discourse on social-emotional learning in Indonesian primary education, with implications for curriculum design and targeted instructional intervention.